Rural caregivers’ preparedness for detecting and responding to the signs of worsening health conditions in recently hospitalised patients at risk for readmission: a qualitative descriptive study - Mary T Fox; Jeffrey I Butler (BMJ Open)
Objectives This study aimed to explore informal rural caregivers’ perceived preparedness to detect and respond to the signs of worsening health conditions in patients recently discharged from hospital and at risk for readmission.Design A qualitative descriptive design and semistructured interviews were used. Data were thematically analysed.Setting Data collection occurred in 2018 and 2019 in rural communities in Southwestern and Northeastern Ontario, Canada.Participants The study included sixteen informal caregivers who were all family members of a relative discharged from hospital at high risk for readmission following hospitalisation mostly for a medical illness (63%). Participants were mostly women (87.5%), living with their relative (62.5%) who was most often a parent (56.3%).Results Three themes were identified: (1) warning signs and rural communities, (2) perceived preparedness, and (3) improving preparedness. The first theme elucidates informal caregivers’ view that they needed to be prepared because they were taking over care previously provided by hospital healthcare professionals yet lacked accessible medical help in rural communities. The second theme captures informal caregivers’ perceptions that they lacked knowledge of how to detect warning signs and how to respond to them appropriately. The last theme illuminates informal caregivers’ suggestions for improving preparation related to warning signs.Conclusions Informal caregivers in rural communities were largely unprepared for detecting and responding to the signs of worsening health conditions for patients at high risk for hospital readmission. Healthcare professionals can anticipate that informal caregivers, particularly those whose relatives live far from medical help, need information on how to detect and respond to warning signs, and may prioritise their time to this aspect of postdischarge care for these caregivers.